A systematic review of computed tomography detection of cartilage invasion in laryngeal carcinoma. (13th January 2015) - Adolphs, Anda P. J.; Boersma, Nienke A.; Diemel, Babette D. M.; Eding, Joep E. C.; Flokstra, Francien E.; Wegner, Inge; Grolman, Wilko; Braunius, Weibel
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis This systematic review aimed to assess the diagnostic value of computed tomography (CT) in detecting cartilage invasion among patients with laryngeal carcinoma. Data Sources PubMed, Embase, and the Cochrane Library. Review Methods A search in the previously mentioned databases was performed to identify relevant articles. Articles comparing cartilage invasion on CT with histology were selected. After critical appraisal, articles of adequate relevance and validity were included in further analysis. Prevalences, sensitivity, specificity, positive predictive values, and negative predictive values were extracted from the included articles. Results Four studies were included in the final analysis. Only one study examined the positive predictive value and negative predictive value for invasion of any laryngeal cartilage, and they were 87% and 56%, respectively. The positive predictive value and negative predictive value for thyroid cartilage invasion were investigated in three studies and ranged from 44% to 80% and from 85% to 100%, respectively. The negative predictive value is likely underestimated due to selection bias, whereas the positive predictive value is likely overestimated. Conclusions CT imaging is a suitable tool to assess laryngeal cartilage invasion, especially regarding the thyroid cartilage. Level of Evidence NA Laryngoscope, 125:1650–1655, 2015